A Canine Distemper Virus Retrospective Study Conducted from 2011 to 2019 in Central Italy (Latium and Tuscany Regions) - Ida Ricci; Antonella Cersini; Giuseppe Manna; Gaetana Anita Marcario; Raffaella Conti; Giuseppina Brocherel; Goffredo Grifoni; Claudia Eleni; Maria Teresa Scicluna (Viruses, 2021)
Canine distemper virus (CDV) is a highly lethal contagious viral pathogen mainly found in domestic and wild canids and mustelids. Although, in Italy, circulating strains of Europe 1, Europe wildlife and Arctic type are reported, data relating to Latium and Tuscany regions are limited. In view of this, through passive surveillance, we investigated the presence of CDV and which strains were circulating in these Regions. From March 2017 to October 2019, a group of 122 subjects were tested for CDV using a PCR protocol described in the literature, with 12 detected positive; analyses were carried out on a set of target samples (brain and lung, conjunctival, nasal and rectal swabs, urine or swab from bladder and intracardiac clot) that was defined for the detection of CDV in both live and dead animals. The rectal swab, easily collected also from live animals, represented the most suitable sample for CDV diagnosis, with 9 positive of the 11 (81.82%) tested. In addition, brain and lung of 15 subjects out of 181 susceptible animals collected between 2011 and 2018, during post mortem investigations in routine diagnostic activity, were CDV positive. Molecular analyses of all positive samples, using a 287 bp fragment located within the conserved N terminus of the morbillivirus nucleoprotein gene, detected the circulation of strain CDV599/2016 (KX545421.1) belonging to the “Europe wildlife” lineage, and of strain CDV12254/2015 (KX024709.1), belonging to the Arctic-lineage, thus confirming the co-circulation of the two lineages, as already noted in previous studies.